Safety of HIF prolyl hydroxylase inhibitors for anemia in dialysis patients: a systematic review and network meta-analysis - Chen, Dinghua; Niu, Yue; Liu, Fei; Yang, Yue; Wang, Xue; Li, Ping; Chen, Xiangmei (Frontiers in Pharmacology, 2023)
Aim: We performed a systematic review and network meta-analysis, evaluating the safety and efficacy of Hypoxia-inducible factor prolyl hydroxylase inhibitors (HIF-PHIs) among dialysis chronic kidney disease (CKD) patients. Methods: Safety was evaluated with any adverse events (AEs), serious adverse events (SAEs), and twelve common events. Efficacy was mainly analyzed with hemoglobin (Hb) response. All reported results were summarized using mean difference (MD) and risk ratio (RR) with 95% confidence interval (CI). Publication bias was assessed through funnel plots. Results: Twenty trials with 14,947 participants were included, comparing six HIF-PHIs with Erythropoiesis-stimulating agents (ESAs). No significant differences were indicated in AEs and SAEs between each HIF-PHI and ESA. The occurrence of gastrointestinal disorder was higher in Enarodustat and Roxadustat than in ESAs (RR: 6.92, 95% CI: 1.52-31.40, p=0.01; RR: 1.30, 95% CI: 1.04-1.61, P=0.02). The occurrence of hypertension was lower in Vadadustat than in ESAs (RR: 0.81, 95% CI: 0.69-0.96, p=0.01). The occurrence of vascular-access complications was higher in Roxadustat (RR: 1.15, 95% CI: 1.04-1.27, p＜0.01) while lower in Daprodustat (RR: 0.78, 95% CI: 0.66-0.92, p＜0.01) than in ESAs. In the risk of the other nine events, including cardiovascular events, no significant differences were observed between HIF-PHIs and ESAs. For efficacy, network meta-analysis showed that the overall performance was similar to ESAs. Compared with ESAs, significant increases were shown in Hb response in Roxadustat (RR: 1.04, 95% CI: 1.01-1.07, p<0.01) and Desidustat (RR: 1.22, 95% CI: 1.01-1.48, p=0.04), whereas noticeable reductions were indicated in Vadadustat (RR: 0.88, 95% CI: 0.82-0.94, p<0.01) and Molidustat (RR: 0.83, 95% CI: 0.70-0.98, p=0.02). There was no significant difference between Daprodustat and ESAs (RR: 0.97, 95% CI: 0.89-1.06, p=0.47). Conclusion: Although HIF-PHIs did not show significant differences from ESAs in terms of overall AEs and SAEs, statistical differences in gastrointestinal disorder, hypertension, and vascular-access complications were observed between HIF-PHIs, which deserved to be noted in clinical decision-making.